Inhibition of hepatitis C virus RNA replication by ISG15 does not require its conjugation to protein substrates by the HERC5 E3 ligase - Domingues, Patricia (J Gen Virol, 2015)
Chronic infection of the liver by hepatitis C virus (HCV) induces a range of host factors including IFN-stimulated genes such as ISG15. ISG15 functions as an antiviral factor that limits virus replication. Previous studies have suggested that ISG15 could influence HCV replication in both a positive and a negative manner. In this report, we determined the effect of ISG15 on HCV RNA replication in two independent cell lines that support viral genome synthesis by inhibiting ISG15 expression through small interfering RNA, short-hairpin RNA and CRISPR/Cas9 gene knockout approaches. Our results demonstrated that ISG15 impairs HCV RNA replication in both the presence and absence of IFN stimulation, consistent with an antiviral role for ISG15 during HCV infection. ISG15 conjugation to protein substrates typically requires the E3 ligase, HERC5. Our results showed that the inhibitory effect of ISG15 on HCV RNA replication does not require its conjugation to substrates by HERC5.